Redefining Curriculum Integration and Professional Development: In-service Teachers as Agents of Change - Sharon Price Schleigh; Michael Bosse; Tammy Lee (Arizona State University, 2011)
Calls for curriculum integration in K-12 mathematics and science have seen nominal results.  Numerous factors including cycles of practice in teacher development and professional development practices have inhibited the development, dissemination, and implementation of integrated curriculum.  This paper examines the characteristics of the professional development standards of both disciplines; considers inherent hindrances to the implementation of integrated curriculum; generates a novel definition for integrated curriculum; argues that the most effective change agent is in-service professional development; and provides guiding notions for effective in-service professional development.